DAKWAH DI ERA ARTIFICIAL INTELLIGENCE: Proses Adopsi Inovasi, Limitasi, dan Resistensi - Asna Istya Marwantika (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
Abstract : Artificial Intelligence also contributes and has an impact on changing da'wah activities. This study aims to describe the process of adopting innovation, limitations, and resistance to using AI in da'wah activities. The research method used is descriptive qualitative, with data collection techniques in literature studies, documentation, media observation, and thematic analysis techniques. The results of this study are 1) Adoption of AI innovations for da'wah is included in the category of Artificial Narrow Intelligence (ANI) such as translation applications, interpretation of the Qurán, prayer applications, Qibla directions, Islamic chatbots, and applications for reading and memorizing the Qurán. 2) Limitations on using AI for da'wah include: limited understanding of the Islamic religion, potentially biased information, lack of sensitivity and empathy, lack of understanding of cultural contexts, cannot replace human interaction, privacy, and data security issues. Even though it has limitations, AI has objectivity in analyzing, is consistent, and is not influenced by emotions compared to Islamic authorities who have different interpretations, and there is emotional involvement. 3) Resistance to the use of AI in da'wah is yet to be very visible because the representation of Islamic authorities, categorized into the early adopters and innovators category, has not shown too much skepticism and is slow in adopting AI. Abstrak : Artificial Intelligence turut berkontribusi dan memberikan dampak dalam mengubah aktivitas dakwah. Penelitian ini bertujuan mendeskripsikan bagaimana proses adopsi inovasi, limitasi dan resistensi penggunaan AI dalam aktivitas dakwah. Metode penelitian yang digunakan adalah metode kualitatif deskriptif, dengan teknik pengumpulan data berupa studi literatur, dokumentasi dan observasi, dan menggunakan teknik analisis tematik. Hasil penelitian ini adalah 1) Adopsi inovasi AI untuk dakwah masuk dalam kategori Artificial Narrow Intelligence (ANI) seperti aplikasi terjemahan, tafsir Alquran, aplikasi doa, shalat, arah kiblat, chatbot Islami, dan aplikasi baca maupun menghafal Alqur’an. 2) Limitasi penggunaan AI untuk dakwah diantaranya: keterbatasan pemahaman agama Islam, berpotensi bias informasi, tidak memiliki sensitivitas dan empati, kurang meemahami konteks budaya, tidak bisa menggantikan interaksi manusia , masalah privasi dan keaman data. Meskipun mempunyai limitasi tapi AI mempunyai obyektifitas dalam menganalisis, konsisten dan tidak terpengaruh emosi dibanding otoritas Islam yang berbeda penafsiran, dan ada pelibatan emosi. 3)Resistensi penggunaan AI dalam dakwah belum terlalu terlihat karena representasi otoritas Islam yang masuk dalam kategori pengadopsi awal (early adopter) dan inovator, belum terlalu menunjukkan sikap skeptis dan lambat dalam mengadopsi AI.